Study of Operation Subsurface Flow Wetland in Batch Flow System for Municipal Wastewater Treatment - Mehrdadi, N.; Rahmani, A.; Akbar Azimi, Ali; Torabian, Ali (Asian Journal of Chemistry, 2010)
Experimental results from a pilot-scale constructed wetland treatment plant have been described. The study was conducted at two different systems: continuous and batch. The pilot plant consists of two serially connected settled up with subsurface flow wetlands. One bed and pretreatment unit were selected at witness unit. Wastewater with 26 m3/day flowrate and average amount of BOD5 = 250 mg/L, TSS = 320 mg/L, TKN = 35 mg/L, TP = 12 mg/L was selected from municipal network in sabzevar wastewater treatment plant and the pilot was studied for one year from December 2006 to December 2007. Biweekly water samples at the inlet and outlet of each component of the combined system were analyzed for biochemical oxygen demand (BOD5), total suspended solid (TSS), total Kjeldahl nitrogen (TKN), total phosphorus (TP). The average removal efficiency of BOD5, TSS, TKN and TP in continuous flow for witness unit was 77.2, 90, 85, 81 % and in batch flow for research unit was 92, 95, 94 and 92 %, respectively.